STRATEGIES OF TEACHING ENGLISH GRAMMAR AND ITS FUNCTIONS - Firuza Turopova (European Science Publishing, 2024)
Teaching English grammar effectively requires a variety of strategies to cater to different learning styles and needs of students. Here's an annotation of some key strategies along with their functions. Helps students understand grammar rules in real-life contexts rather than isolated drills. Teachers can use authentic texts, dialogues, or real-life situations to teach grammar, showing how grammar rules are applied naturally. Function engages students actively in learning and applying grammar. Activities like group discussions, role plays, and games make grammar learning interactive and enjoyable, promoting active participation and understanding. Addresses diverse learning needs and abilities in the classroom. Teachers can vary the complexity or depth of grammar tasks, provide additional support or challenge based on individual student needs, ensuring inclusive learning. Appeals to visual and auditory learners, enhancing understanding through different senses. Use of videos, diagrams, charts, and multimedia presentations to illustrate grammar concepts visually, making abstract rules more concrete. Integrates grammar learning into meaningful tasks and projects. Students learn grammar through completing tasks such as writing emails, creating presentations, or solving problems, focusing on communication rather than just correctness. Provides guidance for improvement and reinforces correct usage. Giving timely and constructive feedback on grammar errors helps students understand their mistakes and encourages self-correction. Builds knowledge progressively from simple to complex grammar structures.
Keywords: Grammar, strategies, functions, games, interactive tools, grammar apps, authentic materials, activities, grammatical structures, role playing.